The Effect of Thiamine Administration on Delayed Recovery from Anesthesia: A Case report - Usama Bensaad; Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2023)
For anesthesiologists, delayed recovery from general anesthesia frequently poses a challenge because they need to quickly establish the most effective treatment by accurately diagnosing the underlying cause. Nonalcoholic Wernicke’s encephalopathy (WE) is a distressing neuropsychiatric syndrome caused by thiamine deficiency. Despite the fact that many case reports on WE have been published, more research is needed to guide the diagnosis and treatment of nonalcoholic WE. Certain tests can help confirm a diagnosis of nonalcoholic WE. Brain magnetic resonance imaging (MRI), routine blood tests, blood thiamine assessments, and other ancillary investigations are among the tests performed. We aim to highlight a case of delayed recovery from general anesthesia that fully recovered after the administration of thiamine.